Tinjauan Hukum Islam terhadap Akad Istishna’ (Studi pada Jual Beli dan Pemasaran Usaha Mebel CV Dua Putra Jati Jepara) - Ngazizah, Inna Fauziatal; Nurhisam, Luqman; Mubaraq, M. Amirrul (TAWAZUN: Journal of Sharia Economic Law, 2023)
The purpose of this research is to know the sales system and implementation of istishna’ contract in the furniture industry in du putra jati furniture jepara. This study uses a qualitative type of research with an emphasis on the results of data collection from the specified informants which are descriptive with the approach used is the Islamic economics approach and the phenomenological approach. This research was conducted at CV Dua Putra Jati Jepara city. Data collection methods include observation, interviews, and document review. Data analysis techniques used are data reduction, data presentation and verification. Informants and respondents from the study include the owner of the CV Dua Putra Jati Furniture Jepara, employees and customers. The results of this study indicate that the Furniture Industry sales system at CV Dua Putra Jati Furniture begins with receiving orders from consumers via telephone, SMS or WhatsApp with specifications determined by the buyer regarding the size, model and price agreement with the Down Payment (DP) payment system by the maker by 50 percent and the rest is paid off when the goods are finished in work. Products that have been completed in the work will be checked first before being delivered to consumers accompanied by a sales invoice (invoice). Implementation of the istishna’ contract in the sales system at CV Dua putra Jati Furniture Jepara has complied with the principles of buying and selling istishna’ contracts, ordering and payment systems made in accordance with the ordering and payment system in the istishna’ contract.